A comparative analysis of fasciocutaneous versus muscle free flaps in peripheral vascular disease patients. Issue 3 (26th January 2023) - Bovill, John D.; Sayyed, Adaah A.; Huffman, Samuel S.; Deldar, Romina; Haffner, Zoë K.; Truong, Brian N.; Gupta, Nisha; Attinger, Christopher E.; Akbari, Cameron M.; Evans, Karen K.
Abstract: Objective: Chronic lower extremity (LE) wounds are common in patients with peripheral vascular disease (PVD). Free tissue transfer (FTT) provides healthy soft tissue for wound coverage and additional blood supply to promote wound healing. Given previous studies demonstrate increased complications in LE fasciocutaneous flaps, it was hypothesized that low vascular resistance in muscle flaps may be more advantageous for wound healing in PVD patients. Therefore, this study compared outcomes in PVD patients undergoing LE reconstruction with fasciocutaneous versus muscle free flaps. Methods: Retrospectively reviewed PVD patients undergoing FTT between 2011 and 2021. Patients were stratified into fasciocutaneous and muscle free flap groups. Primary outcomes included complications, flap success, post‐reconstruction vascular interventions, limb salvage, and ambulatory status. Results: One hundred thirteen patients with PVD were identified, of which 60.2% received fasciocutaneous ( n = 68) and 39.8% received muscle flaps ( n = 45). Forty‐two patients (37.2%) underwent pre‐flap endovascular interventions. Flap success rate was 98.2% ( n = 111). Overall complication rate was 41.2% following fasciocutaneous flaps compared to 24.4% in muscle flaps ( p = 0.067). Fasciocutaneous flaps had higher odds of ulceration requiring repeat angiogram within 1 year of reconstruction compared to muscle flaps (OR 3.4, 95% CI: 1.07–10.95, p = 0.047), and higher odds of requiring repeat angiogram overall (OR 3.4, 95% CI: 1.07–10.95, p = 0.047). No difference in requiring procedures in the operated limb within 1 year was observed ( p = 0.155). At mean follow‐up, there was no difference in limb salvage, ambulatory, and mortality rate between groups. Conclusion: This study demonstrates that fasciocutaneous flaps had higher postoperative complication rates and more commonly required repeat arteriograms following LE FTT reconstruction due to recurrent ulcerations, suggesting greater utility of muscle flaps for FTT reconstruction in PVD patients.